PERBAIKA LINGKUNGAN KERJA GUNA MENINGKATKAN PRODUKTIVITAS DAN KESEJAHTERAAN PENGRAJIN ATAP DAUN NIPAH TRADISIONAL DI DESA PULAU PALAS DENGAN METODE WORK SAMPLING - Randi Sofian (Program Studi Teknik Industri, 2019)
Work productivity is the ability of employees to produce compared to the inputs used, an employee can be said to be productive if they are able to produce goods or services as expected in a short or appropriate time. Productivity is not a calculation of quantity, but a ratio, a comparison and a systematic measurement of a level of efficiency. Production is related to quantity, while productivity is related to the results of unity from an input (Sinungan, 1990: 93). Thus the determination of productivity is faced with the desired results achieved (effectiveness) and the resources used to achieve these results (efficiency). Measurements using measures of efficiency and effectiveness are two dimensions of productivity that are very important in managerial business where they can show productivity indexes which are the ratios to the extent to which resources are used in conjunction with achieving predetermined goals. The results of the research are obtained from the productivity level of workers of palm leaf weavers using the side work method for two months, each study for 7 hours, namely coconut covering workers working productively with 95% yield and delay ratio of 0.07%, and allowance the nipah leaf weaver is 23.6% with the following details: 12.00% of energy released, 4.5% work attitude, 1.3% work movement, 0% eye fatigue, temperature condition the workplace is 5.50%, the atmosphere is 0.5%, and the environment is good at 2.50%.